2019
DOI: 10.1007/s11263-019-01191-3
|View full text |Cite
|
Sign up to set email alerts
|

A Spatiotemporal Convolutional Neural Network for Automatic Pain Intensity Estimation from Facial Dynamics

Abstract: Devising computational models for detecting abnormalities reflective of diseases from facial structures is a novel and emerging field of research in automatic face analysis. In this paper, we focus on automatic pain intensity estimation from faces. This has a paramount potential diagnosis values in healthcare applications. In this context, we present a novel 3D deep model for dynamic spatiotemporal representation of faces in videos. Using several convolutional layers with diverse temporal depths, our proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…Similarly, Zu et al [69] concluded that 33 of chest CTs can have rounded lung opacities. Machine learning (ML) techniques are attracting substantial interest in the medical field, where deep learning-based models have been successfully utilized in many healthcare applications such as depression detection [36], pain estimation [54], breast cancer detection [10], Alzheimer's disease classification [18], and pneumonia detection from chest X-ray images [2]. Due to the increase in COVID-19 cases, healthcare systems have been overwhelmed and require alternative solutions for the automated diagnosis of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Zu et al [69] concluded that 33 of chest CTs can have rounded lung opacities. Machine learning (ML) techniques are attracting substantial interest in the medical field, where deep learning-based models have been successfully utilized in many healthcare applications such as depression detection [36], pain estimation [54], breast cancer detection [10], Alzheimer's disease classification [18], and pneumonia detection from chest X-ray images [2]. Due to the increase in COVID-19 cases, healthcare systems have been overwhelmed and require alternative solutions for the automated diagnosis of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the amount and diversity of sensors used during the data collection phase, several signals have been assessed and evaluated in various settings for the development of pain assessment systems. Some of the most prominently used signals constitute of the audio signal (e.g., paralinguistic vocalizations) (Tsai et al, 2016 , 2017 ; Thiam et al, 2017 ; Thiam and Schwenker, 2019 ), the video signal (e.g., facial expressions) (Rodriguez et al, 2017 ; Werner et al, 2017 ; Tavakolian and Hadid, 2019 ; Thiam et al, 2020b ), specific bio-physiological signals such as the Electrodermal Activity (EDA), the Electrocardiogram (ECG), the Electromyography (EMG), or the Respiration (RSP) signal (Walter et al, 2014 ; Campbell et al, 2019 ; Thiam et al, 2019a ), and also bodily expression signals (Dickey et al, 2002 ; Olugbade et al, 2019 ; Uddin and Canavan, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This competence is termed as few-shot class-incremental learning (FSCIL) [1]. It is also crucial for deep models to acquire this ability in some real applications, such as medical image analysis [2,3,4] and autonomous driving vehicles [5,6,7]. Collecting labeled data for such applications is laborious due to several challenges, including timely and expensive processes, privacy issues, and expert knowledge demanded.…”
Section: Introductionmentioning
confidence: 99%
“…The contributions of our work are three folds: (1) For the first time, we put forward a challenging and practical learning problem called SSFSCIL, which uses unlabeled data along with labeled training data in FSCIL to improve the efficiency and performance; (2) We incorporate a simple but efficient self-training strategy in SSFSCIL for more effective semisupervised learning; (3) We perform extensive experiments on three benchmark datasets to evaluate the performance of our proposed method for image classification and introduce new baselines in this new research direction.…”
Section: Introductionmentioning
confidence: 99%